The relationship with learning of nurses and nursing students - Isaquiel Macedo da Rosa; Maria Elsabeth Cestari (Online Brazilian Journal of Nursing, 2007)
Nursing has historically prioritized the use of practical activities as the way to teach and learn. As we try to understand the formation, and its impact in the professional performance, it is important to question what and how we have been teaching. The idea of relationship with knowledge, taken in its broad sense of relationship with learning, presented by Bernard Charlot allows for a different approach to the teaching-learning process and its product. Therefore, this study had as its goal the analysis of the relationship with learning established by students and nurses that attended the same undergraduate course in nursing. The results pointed to a dependence of students in the first semesters with the figure of the professor while the students from the last semesters showed more independence. On the other hand, graduated nurses signaled the practice as a fundamental factor in the learning process.